Contribution of outstanding political figures to the economic history of the Belarusian lands - Kovalev, Mikhail M. (Journal of the Belarusian State University. Economics, 2024)
The economic history of the Belarusian lands associated with the reign of prominent political figures is studied. Their main achievements are considered. Using a consensus approach (aggregation of different opinions and assessments) the key parameters of economic development (GDP per capita in current US dollars, life expectancy and population size) of the Belarusian territories in different periods are identified.
Keywords: economic history; welfare of Belarusians; historical reforms